Changing Energy Suppliers of Residential Consumers: The Case of Poland - Parkitna, Agnieszka; Gadek, Magdalena; Urbańska, Kamila; Korytko, Paweł; Górski, Arkadiusz (Zielona Góra: Faculty of Economics and Management Press)
During the Russian-Ukrainian conflict, energy prices are rising. Such a situation would suggest high customer turnover, especially since the environment has a strong influence on population behaviour at the individual level. The purpose of this paper is to model the barriers and preferences of individual customers in switching energy suppliers according to the level of satisfaction in a dynamically changing environment. We statistically designed the study using Eta index calculations, test: KruskalWallis, post hoc Dunn`s test with Bonferroni correction.
Keywords: barriers for change; preferences for change; energy market; changes; individual energy behavioural; individual consumers